Towards Development of a Multilingual Mobile Chat Application for Enhanced Global Communication - Oryina Kingsley Akputu; Divine Dumzo-Ajufo; Christian C. Okafor; Adeboye Daniel Abayomi; Terhemba M. Ape (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2024)
The advent of mobile chat applications has revolutionized everyday communication. These applications facilitate the exchange of user's textual and multimedia content across languages and cultures. Most chat applications are known to only support a limited set of predominantly spoken languages, thereby, leaving a substantial portion of the user population without adequate multilingual support. This paper aims to bridge the linguistic gap by presenting Kobapp, a multilingual chat application. The Kobapp, leverages some of the cutting-edge technologies, such as React-Native, Next.js, and the DeepL API, to offer real-time, accurate translations while at the same time offering user privacy. The development process of the Kobapp is outlined from the system architecture and design, emphasizing the integration of a client-side (Android) and server-side using Node.js, Express.js, and MongoDB. Notably, user feedback plays a crucial role in shaping an application's features and functionality. Therefore, the application’s performance was evaluated through a conducted user study. Results of the study indicate a strong positive linear relationship between overall user satisfaction and translation accuracy for different language pairs. Moreover, the absence of outliers and the model's significance further reinforces the application's commitment to data quality and accuracy. Future research will explore new dimensions in multilingual communication and applications to promote a truly global community.